ISO 26000: the new face of corporate social responsibility? - Schömann, Isabelle (Brussels, 2012)
"This first ETUI Policy Brief of 2012 deals with the first ISO international social standard ‘ISO 26000 – Guidance for Social Responsibility’ (GSR). The author argues, that unlike other standards, it is political rather than technical, taking on the role of organisations within society even though it is not intended for certification purposes. In addition, ISO 26000 brings about deep-seated changes aimed at altering the entire landscape of corporate social responsibility (CSR) as developed within and by the European Union. Some see it as an unrivalled revolution designed to frame the activities of market and non-market players in society, in a determined step towards sustainable development. Others see it rather more as a game of deceit, not merely because of the derogatory procedure put in place to set the norm but also in terms of the confusion established between legal responsibility and social responsibility and, finally, with a view to the degree of generalisation in respect of issues and stakeholders, which draws attention away from multinational companies."